Islamic Banking And Financial Stability In Indonesia: A Systematic Literature Review Approach (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to explore the financial stability of Islamic banks in Indonesia through a systematic literature review of empirical studies published between 2019 and 2024. Using a structured approach, six peer-reviewed studies were analyzed based on their models, variables, and findings. The results show that internal bank factors such as capital adequacy, operational efficiency, and credit risk are the most consistent determinants of stability. Macroeconomic variables, particularly inflation and exchange rate volatility, also play a significant role. Interestingly, Sharia-related factors—such as Islamicity performance—emerged as positive contributors to bank stability, highlighting the unique nature of Islamic finance. However, financial inclusion and GDP growth showed mixed or insignificant effects. This review suggests that improving internal management, strengthening Sharia compliance, and enhancing risk mitigation are essential for building a more stable Islamic banking sector in Indonesia.